Effects of Brief Behavioural Activation on Approach and Avoidance Tendencies in Acute Depression: Preliminary Findings. Issue 1 (3rd October 2016) - Nasrin, Farjana; Rimes, Katharine; Reinecke, Andrea; Rinck, Mike; Barnhofer, Thorsten
Abstract : Background: It has been suggested that the behavioural activation (BA) treatments for depression unfold their effects, at least partly, through changes in approach and avoidance tendencies. However, as yet, little research has examined the cognitive effects of these interventions.Aims: This study investigated the impact of a single session of BA on depressive symptomatology, self-reported avoidance, and behavioural approach and avoidance tendencies.Method: Forty-six patients with a diagnosis of Major Depression were recruited from primary care psychological therapies services and block randomized to either a single session of behavioural activation ( n = 22) or waiting list control ( n = 24) delivered by an unblinded therapist. Self-reports of symptoms and cognitive factors were assessed before and after the one-week intervention phase. Approach and avoidance behavioural tendencies were assessed using the Approach-Avoidance Task (AAT).Results: Data from 40 participants ( n = 20 in each group) was available for analyses. Depressive symptoms significantly decreased, and activation significantly increased from before to after treatment in the treatment group, but not in the control group. Performance on the AAT showed a trend indicating increased approach to positive valence stimuli in the treatment group, but not in the control group. Mediational analyses indicated small indirect effects of self-reported change in activation as mediators of the effect of condition on symptoms.Conclusions: The findings suggest that a single session of BA can have significant effects on symptoms in clinically depressed patients. Results hint at the possibility that increased behavioural approach might mediate the effect of BA.